removal of metal ions from ethanoic acid producing plant waste water effluent,using ion exchange resins and activated carbon - utheswaran krishna moorthy, utheswaran krishna moorthy (2009)
This study is conducted using effluents taken from BP PETRONAS Acelyls Plant which the outcomcs of this project may give new alternative for effluent treatment oil-site not only for BBPA plant but to other industries as well This is to ensure the quality of the environment is maintained and at the same time may help in reducing cost of having to treat the effluent off site.